2011
DOI: 10.1021/jp210129r
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Charge Distribution and Electrostatic Potential in Silicates with the Use of Chemical Potential Equalization Models

Abstract: New parameters for the electronegativity equalization model (EEM) and the split-charge equilibration (SQE) model are calibrated for silicate materials, based on an extensive training set of representative isolated systems. In total, four calibrations are carried out, two for each model, either using iterative Hirshfeld (HI) charges or ESP grid data computed with Density Functional Theory (DFT) as a reference. Both the static (ground state) reference quantities and their responses to uniform electric fields are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 68 publications
5
77
0
Order By: Relevance
“…A recent calibration of EEM and SQE parameters for silicates revealed that Hirshfeld-I charges systematically overestimate (in absolute value) the MEP of silica clusters. 12 Similar observations were made during the development of a forcefield for MIL-53(AL). 119 It is clear that there is still room for improved partitioning schemes that enhance the trade off between the sphericity and locality of the AIMs.…”
Section: Therefore 4πr 2fsupporting
confidence: 59%
See 3 more Smart Citations
“…A recent calibration of EEM and SQE parameters for silicates revealed that Hirshfeld-I charges systematically overestimate (in absolute value) the MEP of silica clusters. 12 Similar observations were made during the development of a forcefield for MIL-53(AL). 119 It is clear that there is still room for improved partitioning schemes that enhance the trade off between the sphericity and locality of the AIMs.…”
Section: Therefore 4πr 2fsupporting
confidence: 59%
“…This result can be seen as a generalization of the expressions proposed by Itskowitz et al 79 Conventionally, EEM parameters are obtained through daunting least-squares fits, in which correlations between chemical potential and hardness parameters are practically unavoidable. 8,12,77 The spherical atom EEM provides an alternative for these cumbersome calibration procedures. In analogy with the seminal paper of Mortier, 4 we also observe that the intrinsic chemical potential and hardness of an atom in a molecule must be corrected for the molecular environment.…”
Section: Therefore 4πr 2fmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a distinct advantage of HI over QTAIM and implies that HI charges are both useful for a direct chemical interpretation as well as for the development of force field models. Unfortunately, a recent study revealed that HI charges severely overestimate molecular dipoles of isolated inorganic clusters [16], showing that the accurate reproduction of the molecular ESP is not a universal property of the HI scheme. Because of this deficiency, it is clear that the Hirshfeld-I scheme can be improved.…”
Section: Introductionmentioning
confidence: 99%